Identify the knowledge level of rural leaders towards paddy farming technologies in Muda Agriculture Development Authority (MADA-Malaysia) - Masso, Wisam Yako Aziz; Man, Norsida (Indian Society for Education and Environment, 2016)
Rural leaders are the people who are able in an informal manner that the influence relatively frequently on the behavior and attitudes of others towards what is desirable. However, the study was conducted to determine the knowledge perception levels of rural leaders of paddy farming technologies in muda agriculture development authority (MADA). The sample size of this study is (260). The random Sampling technique was used in this study. This research also was done by interview approaches to gain the knowledge perception levels of rural leaders of paddy farming technologies. Using SPSS, descriptive and inferential analyses was performed to fulfill the objectives determined. Based on the results gained, the knowledge level of paddy farming technologies among respondents is moderate. Further analysis done have proved that there is a significant relationship between some social, demographic factors and level of knowledge of respondents on paddy farming technologies, it is recommended that rural community access and exposure to agricultural technologies must be strengthened, so that our future generations will have good knowledge on paddy farming technologies to have the best paddy.